Abruptio Placentae Caused by Hypertriglyceridemia-Induced Acute Pancreatitis during Pregnancy: Case Report and Literature Review. (5th September 2018) - Yalcin Bahat, Pınar; Turan, Gokce; Aslan Cetin, Berna
Abstract : Background . Hormonal effects during pregnancy can compromise otherwise controlled lipid levels in women with hypertriglyceridemia and predispose to pancreatitis leading to increased morbidity for mother and fetus. Elevation of triglyceride levels is a risk factor for development of pancreatitis if it exceeds 1000 mg/dL. Pancreatitis should be considered in emergency cases of abdominal pain and uterine contractions in Emergency Department at any stage of pregnancy. We report a case of abruptio placentae caused by hypertriglyceridemia-induced acute pancreatitis. Also, literature review of cases of acute pancreatitis induced by hypertriglycaemia in pregnancy has been made. Case . A 22-year-old woman presented to our Emergency Department, at 35 weeks of gestation, for acute onset of abdominal pain and uterine contractions. Blood tests showed a high rate of triglyceride. The patient was diagnosed with abruptio placentae caused by hypertriglyceridemia-induced acute pancreatitis. Immediate cesarean section was performed and it was observed that blood sample revealed a milky turbid serum. Insulin, heparin, and supportive treatment were started. She was discharged on the 10th day. Conclusion . Consequently, patients with known hypertriglyceridemia or family history should be followed up more closely because any delay can cause disastrous conclusions for mother and fetus. Acute pancreatitis should be considered in pregnant women who have sudden onset, severe, persistent epigastric pain and who have a risk factor for acute pancreatitis.